A validated UPLC–MS/MS method for flibanserin in plasma and its pharmacokinetic interaction with bosentan in rats. (July 2018) - Iqbal, Muzaffar; Ezzeldin, Essam; Rezk, Naser L; Bajrai, Amal A; Al-Rashood, Khalid A
Aim: The purpose of this study was development, validation and application of ultra-performance liquid chromatography (UPLC)–ESI–MS/MS method for quantitation of flibanserin in plasma samples.Method & results: After extraction of analyte from plasma by diethyl ether, separation was performed on UPLC C18 column using mobile phase composition of 10 mM ammonium formate-acetonitrile (30:70, v/v) by isocratic elution of 0.3 ml/min. The multiple reaction monitoring transitions of m/z 391.13 → 161.04 and 384.20 → 253.06 were used for detection of analyte and internal standard (quetiapine), respectively. The calibration curves were linear (r ≥ 0.995) between 0.22 and 555 ng/ml concentration and all validation results were within the acceptable range as per US FDA guidelines.Conclusion: The assay procedure was fully validated and successfully applied in pharmacokinetic interaction study of flibanserin with bosentan in rats.